ETIKA PENGGUNA SOSIAL MEDIA DI KALANGAN SISWA SMA DI KOTA PADANG, SUMATERA BARAT - Delpa Delpa; Eda Elysia (JISOS: JURNAL ILMU SOSIAL, 2022)
Development Technology of communication give us the chance and space to do access information based on digital aspect. Each the user of social media gets a high freedom to express themself, learn many thing, dan do interaction with each other. Otherwise, there are so many the user of media social do not realize that the all everything they have done in digital space will recording by the system and can’t do deleting process. Besides that, there is no technology equipment able to delete our activities in digital space. This is one of the big problem for the user when do the negative activities in digital space, especially for student. Objective of this research is to analyze how about their activities when using media social. Method of collecting the data by google form for 1000 student SMA in Padang City. Informant of research is student in Padang city and method analyze is qualitative method. The result by google form application explain that 60 percentage the user involved with online game, 20 % related with download pornography content and 20 percentage come from bully activities. The solution of this problem is the family institution must be able to control their children when they use social media. Besides that, parent able to be a good rule model doing ethics digital using social media for all the member of family institution